Perubahan Kadar Nitrogen Total Pada Tanah Sebagai Alternatif Estimasi Post-Mortem Interval - Durrotus Sunniyyah (Jurnal Biosains Pascasarjana, 2021)
AbstractForensic taphonomy is a branch of forensic science which in its application uses processes related to the decomposition of corpses and uses soil evidence to estimate post-mortem interval (PMI) or post burial. Soil has evidential value because it contains minerals, plants and animal materials that are useful for characterization. This research was conducted by analyzing soil characteristics, namely soil pH and soil moisture and total nitrogen content in soil samples taken from under rabbit carcasses that were placed on the soil surface, buried 25 cm and 50 cm at each decomposition stage. The results obtained showed significant differences at each stage of decomposition and laying of the carcasses.